Trends, Opportunities, and Challenges of Using WhatsApp in Learning: A Literature Review - Nasution, Awal Kurnia Putra; Munandar, Imam (Jurnal Simki Pedagogia, 2023)
WhatsApp is a widely used and widely used communication platform in education. The main objectives of this literature review are to identify the trends and challenges associated with using WhatsApp in education, explore the benefits and opportunities for students and teachers in using this platform for learning, and understand the challenges and limitations of using WhatsApp within the classroom setting. The literature was obtained through various databases using keywords related to WhatsApp and education. It is important for educators and administrators to be aware of the trends, opportunities, challenges, and opportunities associated with the using of WhatsApp. The increased usage of WhatsApp as a tool for communication and collaboration between students and teachers is one trend that has been identified in the research. The results of this literature review will contribute to the field of education and technology by highlighting the potential of WhatsApp as a tool for learning and providing insights on how it can be effectively integrated in classroom instruction. The article also discusses the need to consider privacy and security issues when using WhatsApp in education, and provides suggestions for further research.